2021
DOI: 10.1101/2021.02.25.21252481
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Excess deaths reveal the true spatial, temporal, and demographic impact of COVID-19 on mortality in Ecuador

Abstract: BackgroundIn early 2020, Ecuador reported one of the highest surges of per capita deaths across the globe.MethodsWe collected a comprehensive dataset containing individual death records between 2015 and 2020 from the Ecuadorian National Institute of Statistics and Census and the Ecuadorian Ministry of Government. We computed the number of excess deaths across time, geographical locations and demographic groups using Poisson regression methods.ResultsBetween January 1st and September 23rd, 2020, the number of e… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
16
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 24 publications
1
16
0
Order By: Relevance
“…By October 2020, Ecuador had more than 166 excess deaths per 100 000 population, becoming one of the countries with the highest number of coronavirus disease 2019 (COVID-19) related deaths. 1 3 Official data at the time of the study reported more than 170 000 confirmed COVID-19 cases and more than 8000 related deaths; however, these numbers are expected to be much higher. 3 Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) diagnosis has mainly targeted large urban areas such as Guayaquil, Quito or Cuenca, the only cities where free testing is available through the National Institute of Public Health Research.…”
mentioning
confidence: 98%
See 4 more Smart Citations
“…By October 2020, Ecuador had more than 166 excess deaths per 100 000 population, becoming one of the countries with the highest number of coronavirus disease 2019 (COVID-19) related deaths. 1 3 Official data at the time of the study reported more than 170 000 confirmed COVID-19 cases and more than 8000 related deaths; however, these numbers are expected to be much higher. 3 Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) diagnosis has mainly targeted large urban areas such as Guayaquil, Quito or Cuenca, the only cities where free testing is available through the National Institute of Public Health Research.…”
mentioning
confidence: 98%
“… 1 3 Official data at the time of the study reported more than 170 000 confirmed COVID-19 cases and more than 8000 related deaths; however, these numbers are expected to be much higher. 3 Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) diagnosis has mainly targeted large urban areas such as Guayaquil, Quito or Cuenca, the only cities where free testing is available through the National Institute of Public Health Research. Despite the institute’s efforts to improve testing capacity, 4 no more than 3000 polymerase chain reaction (PCR) tests have been performed per day in Ecuador, for a population of 17 million.…”
mentioning
confidence: 98%
See 3 more Smart Citations